Mecanismos de envejecimiento de la piel - Mesa-Arango, Ana Cecilia; Flórez-Muñoz, Sindy Viviana; Sanclemente, Gloria (Iatreia, 2017)
Skin aging is an inevitable biological phenomenon of human life that results from either the age-dependent decline of cell function (intrinsic aging) or from cumulative exposure to external harmful influences (extrinsic aging). Intrinsic and extrinsic factors act synergistically to induce skin changes that manifest clinically as burns, erythema, hyperpigmentation, telangiectasia, skin dryness or sagging, coarse wrinkles, skin texture changes or eventually as skin cancer. The molecular mechanisms of both types of skin aging are similar. This review focuses on intrinsic and extrinsic mechanisms of skin aging, and on current and new perspectives for prevention and treatment options extracted from natural products.